2016
DOI: 10.1016/j.placenta.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of human placental PAPP-A2 over gestation and in preeclampsia

Abstract: Introduction Pregnancy Associated Plasma Protein A2 (PAPP-A2) is a pregnancy related insulin-like growth factor binding protein-5 (IGFBP-5) protease, known to be elevated in preeclampsia. As the insulin-like growth factors are important in human implantation and placentation, we sought to determine the expression pattern of PAPP-A2 over human gestation in normal and preeclamptic pregnancies to evaluate its role in placental development and the pathogenesis of preeclampsia. Methods Placental basal plate and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
6
20
2
Order By: Relevance
“…PAPP-A2 acts in the regulation of growth factors during trophoblast invasion. The levels were elevated in maternal sera and placental tissue during PE [119].…”
Section: Prediction and Putative Biomarkersmentioning
confidence: 95%
“…PAPP-A2 acts in the regulation of growth factors during trophoblast invasion. The levels were elevated in maternal sera and placental tissue during PE [119].…”
Section: Prediction and Putative Biomarkersmentioning
confidence: 95%
“…Among these genes, PAPPA-2 is the gene with the largest number of methylation sites significantly altered (hypomethylation), and with the largest number of transcripts significantly differently expressed (overexpression) in IUGR placentas. Its overexpression has already been reported in both maternal blood and the placenta in IUGR (Whitehead et al, 2013) and PE (Kramer et al, 2016). PAPPA-2 encodes a protein cleaving the insulin-like growth factor 1 (IGF-1) from a ternary complex with IGF binding proteins (IGFBP-3) (Fujimoto et al, 2017).…”
Section: Energy Metabolism and Insulin Resistancementioning
confidence: 99%
“…STC1 was reported to inhibit the proteolytic activity of PAPP-A and PAPP-A2 in vitro (12). Reduced maternal serum PAPP-A levels refer to a high PE risk (21), whereas maternal sera and placental tissues from PE cases show, in contrast, elevated levels of PAPP-A2 (22). We speculate that increased circulating STC1 in PE pregnancy may represent a feedback mechanism to high expression of PAPP-A2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated that STC1 is a proteinase inhibitor of the pregnancy-associated plasma protein (PAPP)-A and PAPP-A2, modulating IGF signaling (12). Both encoding genes, PAPPA and PAPPA2 , are among the most highly expressed genes in the human placenta (20), and their altered expression has been linked to PE (21, 22). …”
mentioning
confidence: 99%